Multi-Agent Systems in Control Engineering: A Survey - Fatemeh Daneshfar; Hassan Bevrani (Journal of Control Science and Engineering)
This paper presents a survey on multi-agent system (MAS) capabilities in control engineering applications. It describes essential concepts of multi-agent systems that are related to the control systems and presents an overview on the most important control engineering issues which MAS can be explored. Most important technical aspects in MAS implementation and development in engineering environment are also explained. Design methodologies, standards, tools, and supporting technologies to provide an effective MAS-based control design are addressed and a discussion on important related standards and protocols is given. Finally, some comments and new perspectives for design and implementation of agent-based control systems are presented.